The approach to undergraduate research projects at Namibia's first School of Medicine - MA Kandingo; Q Wessels; LNN Shipingana; OKH Katali (South African Medical Association, 2023)
Background. The integration of undergraduate research (UR) in biomedical curricula has gained much interest.Objective. To investigate the research focus of compulsory UR in the medical curriculum of the University of Namibia's School of Medicine.Methods. A retrospective mixed-methods document review was performed on 42 research projects using the 5C framework that assessed students' abilityto Cite, Compare, Contrast, Critique and Connect in their research reports.Results. Students' research projects focused on internal medicine (29%; n=12), paediatrics (26%; n=11), obstetrics and gynaecology (19%; n=8), surgery(10%; n=4), psychiatry (5%; n=2) and oncology (2%; n=1). A final category is other, which included health professions education and anatomy (10%; n=4).Students' reports had aims, objectives or goals that were correctly done. Students' review of the literature reflected their ability to cite relevant scholarlyworks and to compare these by highlighting agreements or disagreements. Contrasting and critiquing research findings proved to be challenging.Conclusion. Findings from the current study indicate variability in the degree of students' research competence. It appears that the elements of criticalthinking and appraisal require further strengthening within the existing curriculum